Development of Google Site-Based E-LKPD to Improve Students’ Understanding of Ion Bond Material - Arit, Arit; Masriani, Masriani; Ulfah, Maria; Rasmawan, Rahmat; Sartika, Rody Putra (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This research aims to determine the feasibility of Google site-based E-LKPD on class X ion bond material at SMA Negeri 1 Galing. The population in this study was 25 class X students and samples were taken using a random sampling technique totaling 5 people. This research uses the R & D (Research and Development) research method with the ADDIE model which focuses on the Analysis, Design and Development stages. At the development stage, a feasibility test was carried out by five validators with two assessment aspects, namely material and media using the Content Validity Index (CVI) as a feasibility test.